As definições da leptospirose humana como problema de saúde pública no Brasil - Martins, Mário Henrique da Mata (2018)
The purpose of this thesis was to explore the ways in which causes to a public health problem, people responsible for its existence and specific places and periods for intervention are assigned, engendering certain government strategies to the detriment of others. Our goal was to make visible the effects of these definitions on the actions of a public policy and to problematize the bases that sustain their production. The phenomenon of our study was human leptospirosis, a potentially lethal disease which has been doubly neglected by public policy because of the invisibility of its population profile and its mimetic clinical picture. We adopted discursive practices as our theoretical and methodological framework and focused on the attribution processes presented in the definition of this public health problem and on the versions produced. An analytical tool was developed in order to enable the analysis of these elements in documents of public domain (scientific articles, models of notification and investigation forms, campaign materials) and speeches (interviews with managers, technicians and users of public health services). In our analysis of the Brazilian scientific literature on the subject, we have identified a recurrent attribution of cause to the bacteria, which could lead one to believe that the investment in vaccines and antibiotics would eliminate the problem. However, the plurality of types of bacteria and the controversy over the use of antibiotics in cases of leptospirosis show the limitation of this reasoning. The analysis of the leptospirosis models of notification and investigation forms made it possible to identify that a biomedical version of the disease was produced with the justification that only clinical-laboratory factors, in detriment of environmental and epidemiological data would be under direct responsibility of the health sector. On the other hand, when analysing posters, folders and leaflets used in the campaigns for the prevention of leptospirosis in a Brazilian municipality, we have identified that they present a preventive version of the disease. In these materials, the communicational model is unidirectional and authoritarian, and the responsibility for infection and prevention actions is attributed to the population, sometimes acknowledging and sometimes neglecting their living conditions. Finally, we have also analysed the attributions of cause and responsibility for the disease in the speeches of managers, technicians and users of health services. Through the analysis, it was possible to identify five common causes and responsibilities addressed by the participants: social conditions, basic sanitation, the rat, the preparation of the health sector and the population. However, the resolution uttered by the majority of managers and technicians was the need to inform, educate and/or punish the population, an attribution that is not presented in the users' speech and points to a lack of dialogue between these groups. Given the multiplicity of attributions and the potential effects they generate for the management of Brazilian health policy, we could defend the thesis that the definition of a health problem is a psychosocial practice in which the attributions and associations between repertoires constitute a central element of dispute, produced in the use of language